Optical parameters of the film naturally formed on the surface of cadmium telluride single crystals - Odarych, V.A.; Poperenko, L.V.; Yurgelevych, I.V.; Gnatyuk, V.A.; Toru Aoki (Functional Materials, 2013)
Ellipsometric study of different surfaces of CdTe single crystals was carried out at a light wavelength of 632.8 nm. CdTe(110) crystals with cleaved surfaces after long time storage under ambient air conditions, Cd- and Te-terminated faces of (111) oriented CdTe crystals aged at room temperature in air during different times and samples chemically etched in a Br–HBr solution were investigated. The refraction and absorption indexes, and thickness of the films formed on the surface of different samples were obtained and the nature of these films was discussed. The ellipsometric measurement data have been well described by the two-layer model of a reflective system which includes (1) internal presumably pure Te layer with thickness of a few monoatomic layers and (2) external layer, probably Cd or Te oxide film of thickness from 5 to 10 nm depending on the time of storage in air.